Systematic review and meta-analysis of the effectiveness of antiseptic agents for meatal cleaning in the prevention of catheter-associated urinary tract infections. Issue 3 (March 2017) - Fasugba, O.; Koerner, J.; Mitchell, B.G.; Gardner, A.
Summary: Background: Catheter-associated urinary tract infections (CAUTIs) are among the most common healthcare-associated infections. Antiseptic cleaning of the meatal area before and during catheter use may reduce the risk of CAUTIs. Aim: To undertake a systematic review of the literature and meta-analysis of studies investigating the effectiveness of antiseptic cleaning before urinary catheter insertion and during catheter use for prevention of CAUTIs. Methods: Electronic databases were searched to identify randomized controlled trials. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated and compared across intervention and control groups using DerSimonian–Laird random-effects model. Subgroup analyses were performed. Heterogeneity was estimated using the I 2 statistic. Findings: In total, 2665 potential papers were identified; of these, 14 studies were eligible for inclusion. There was no difference in the incidence of CAUTIs when comparing antiseptic and non-antiseptic agents (pooled OR 0.90, 95% CI 0.73–1.10; P =0.31), or when comparing different agents: povidone-iodine vs routine care; povidone-iodine vs soap and water; chlorhexidine vs water; povidone-iodine vs saline; povidone-iodine vs water; and green soap and water vs routine care ( P >0.05 for all). Comparison of an antibacterial agent with routine care indicated near significance ( P =0.06). There was no evidence of heterogeneity ( I 2 =0%; P >0.05). Subgroup analyses showed no difference in the incidence of CAUTIs in terms of country, setting, risk of bias, sex and frequency of administration. Conclusions: There were no differences in CAUTI rates, although methodological issues hamper generalizability of this finding. Antibacterial agents may prove to be significant in a well-conducted study. The present results provide good evidence to inform infection control guidelines in catheter management.